Breeding report of a new high-quality, large-fruit and two-season bearing red raspberry cultivar Shenlinna - LIU Zhendong; DAI Hanping (Guoshu xuebao)
Shenlinna is a new high-quality and two-season bearing red raspberry cultivar with largefruit. The seedling was derived from a cross between maternal parent Tulameen and paternal parent Qiuping in 2014 at the raspberry experimental field in Shenyang Agricultural University. Artificial hybridization pollination was done in 2014, and the seeds were sowed in a greenhouse. A total of 512 seedlings were obtained and transplanted in the field in 2015. The cultivar was initially selected in 2016 for its large, uniform, firm and sweet fruit. The fruits had sweet and sour flavor and high quality. Then it was propagated by tissue culture for further investigation. After regional adaptability testing at three sites (including Shenyang, Dalian and Shanghai) over five years from 2019 to 2023, it was finally selected in 2023. The cultivar is a subshrub with thick and tall primocanes, attaining a height of 220 cm. Primocanes are green and with medium dense purple prickles. The length of its fruiting lateral can reach over 1 m. Ternate pinnate leaves are large, with a length of 30 cm, a width of 25 cm and a petiole length of 7 cm. Flower is white with 5 ligulate petals. Fruit uniformity is good. Fruit is red and conical, with firm, thick, waxy and fine flesh. The average fruit weight is 6.0 g, and the maximum fruit weight is 13.0 g. Fruit shape index is 1.3. Each aggregate fruit has 130 drupelets. The contents of soluble solid and total acid are 9.5% and 0.77%, respectively. The solid-acid ratio is 12.3. The content of Vitamin C is 1.2 mg·g-1 (FW). The content of total anthocyanin is 0.63 mg·g-1 (FW). The contents of total phenols and flavonoid are 24.8 and 13.8 mg·g-1 (DW), respectively. The overall quality is excellent. The high quality fresh fruit rate is more than 75%. This cultivar can produce economic yield from floricanes in summer and primocanes in autumn. In Shenyang area, fruits mature from June 20th to July 30th as well as from August 10th to October 15th. Laterals gradually branch out from top to bottom on primocanes, but the developmental process of laterals at different height is more consistent on floricanes. For each fruiting lateral, it flowers from the top to the base. The fruit development period is 28 to 32 d. This cultivar can be well cultivated in north, central and east China. It can flower and bear fruit in the current year after planted. 80% of economic yield can be realized in the next year. Bumper and stable yield can be achieved from the 3rd year, with a yield of 1050 kg per 666.7 m2. A well-drained sandy soil with a pH value of 5.6 to 7.5 and an irrigation condition are proper for the cultivation of this cultivar. Plenty of base fertilizer or substrate such as coco coir is recommended for soil improvement. Spacing in and between the rows are 30-40 cm × 200 cm. Top application should be applied at the stage of leaf unfolding, bud presenting and fruit swelling. Application amount is 20 kg per 666.7 m2 with the N∶P∶K ratio of 1∶2∶2. Dripping and infiltrating irrigation system are recommended. Pay attention to drainage in rainy season. In drought season, irrigation should be done every 3 d.